A computer oriented model of blended learning of the English language - Isakova, Ye.; Zubenko, K. V.; Paziura, N.; Olekhnovych, V.; Ostashchuk, V.; Зубенко, K. В.; Ісакова, Є. П.; Пазюра, Н. В.; Олехнович, В. Д.; Остащук, В. І. (Національний технічний університет «Дніпровська політехніка», 2020)
An analysis of the experience of introducing the blended learning model in the process of learning English by students of a non-linguistic university in terms of the place of this model in the educational process, the relevance of its use in modern higher education conditions, defining basic criteria and requirements for the participants of the educational process to ensure the effective implementation of blended learning and determining conditions for the successful organization and control of training within the framework of the blended learning model. Qualitative and quantitative analysis of the results.

Аналіз досвіду впровадження моделі змішаного навчання у процес вивчення англійської мови студентами немовного ВНЗ з точки зору місця даної моделі в навчальному процесі, доречності її використання в сучасних умовах вищої освіти, визначення базових критеріїв і вимог до учасників навчального процесу задля забезпечення ефективної реалізації змішаного навчання, а також умов успішної організації й контролю навчання в рамках моделі змішаного навчання. Якісний і кількісний аналіз отриманих результатів.
Комп’ютерно-орієнтована модель змішаного навчання іноземної мови
Keywords: blended learning; education system; foreign language; information technologies; змішане навчання; освітня система; іноземна мова; інформаційні технології